Towards Sustainable Project Governance : A Multisystem and Multilevel Analysis - Daneshpour, Hosein (Vaasan yliopisto, 2018)
Multilevel assessment has been put forward in this study as a key tool for tackling the challenges of sustainable development. Therefore, in addition to the micro scale, two other important levels are analysed: the meso and macro levels. Through spatial modelling, this research contributes to the context of project portfolio management and presents a gestalt of systems. The study starts from the analysis of macro scale sustainable development within the European context. Four key elements of the model are introduced: innovation, efficiency, co-creation and environment. This approach also presents a solution to the challenge of the paradigm shift that has increased the complexity of project portfolio management. Subsequently, the front-end of the portfolio has been formulated with a sustainable method. Meanwhile, the trend of eco-efficiency in the EU-15 countries is evaluated, and a longitudinal analysis determines the cases that are promoting sustainability. Furthermore, the challenge of sustainability requires a business model that governs the whole system. Thus, the meso scale has been studied through a systematic review of the literature and exploratory case studies of prominent companies in Europe. Consequently, an open innovation model as a mediator of the Agile method is discussed as a framework. The study gradually narrows down towards the micro scale in Finland. Although the efficiency of various cases has been analysed, another layer of analysis is performed in order to explore the reasons behind the efficiency in Finland. The performances of projects in Finland are assessed through decomposition analysis.

Tämä tutkimus esittää monitasoista arviointia keskeiseksi välineeksi kestävän kehityksen haasteiden ratkaisemiseen. Sen johdolla on analysoitu mikrotason lisäksi kahta muuta tärkeää tasoa: meso- ja makrotasoa. Spatiaalisen mallinnuksen avulla tämän tutkimuksen tarkoituksena on edistää projektisalkunhallintaa sekä muodostaa systeemien kokonaisuus. Tutkimus on aloitettu kestävän kehityksen makrotason analyysilla eurooppalaisessa kontekstissa. Mallin neljä keskeistä elementtiä ovat innovaatio, tehokkuus, yhteiskehittäminen ja ympäristö. Tämä lähestymistapa tarjoaa myös ratkaisun paradigman muutoksen aiheuttamalle haasteelle, joka on lisännyt projektisalkunhallinnan monimutkaisuutta. Tämän seurauksena projektisalkun alkuvaihe on muodostettu kestävää menetelmää hyödyntäen. Samalla on arvioitu ekotehokkuuden kehitystä EU-15 maissa sekä pitkittäisanalyysin avulla määritetty ne tapaukset, jotka ovat edistyneet kestävästi. Kestävän kehityksen haasteet vaativat myös liiketoimintamallin, jolla voidaan hallita koko järjestelmää. Siten mesotasoa on tarkasteltu sekä systemaattisen kirjallisuuskatsauksen että merkittävien eurooppalaisten yritysten avulla. Sen seurauksena viitekehityksenä on käsitelty avointa innovaatiomallia ketterän mallin muuntavana tekijänä. Tutkimus kapenee asteittain kohti mikrotasoa Suomessa. Vaikka monien eri tapauksien tehokkuutta onkin jo analysoitu, tehdään toinen analyysi tehokkuuden syiden selvittämiseksi Suomessa. Projektien suorituskykyä Suomessa on arvioitu dekompositioanalyysillä.
Keywords: open innovation; spatial analysis; efficiency analysis; green energy economy; contingency theory; change management; sustainable development; renewable portfolio; innovaatiot; energiatalous; muutoksenhallinta; projektinhallinta